A follow-up evaluation of a coordinated police-social services response to recidivist family violence - Hamilton, Gemma (Journal of criminology, 2023)
Coordinated multi-agency approaches are a key strategy for responding to recidivist family violence. This paper presents a follow-up quantitative evaluation of Alexis: a coordinated police-social services approach to recidivist and high-risk family violence piloted in Victoria, Australia. State-wide police data was collected for 75 perpetrators 20 to 36 months since case closure following Alexis intervention. Results indicated that 38 perpetrators (51%) had no further recorded incidents of family violence. The remaining non-mutually exclusive categories indicated that 17 (22%) had perpetrated family violence against the original Alexis victim in another location (outside the pilot catchment zones); 28 (37%) had perpetrated family violence against a different victim; and 8 of the prior two groups (11%) had perpetrated violence against both Alexis and non-Alexis victims. Those classified as low recidivists before intervention were less likely to have a further recorded incident of family violence during the follow-up period compared to high recidivists. Implications for police and policy-makers are discussed with reference to intimate partner violence and parent abuse by adult children.